Digitalization of Savings and Loans to Improve Financial Management of PKK Candi Lontar, Sambikerep Surabaya - Prayogi, Gusti Dian; Resmawa, Ira Ningrum; Febriana, Annisah (Sarana Ilmu Indonesia (salnesia), 2025)
Training to introduce savings and loan accounting applications is a form of community service activity carried out by lecturers from STIE YAPAN. The partners in this activity are the management and members of the PKK RW 07 Candi Lontar savings and loan group. The savings and loan activity is an economyc activity commonly carried out by PKK women in RW 07 Candi Lontar. However, manual transaction recording often causes difficulties in financial management and reporting. Therefore, this community service activity aimed to provide training on the use of savings and loan accounting applications to PKK women in RW 07 Candi Lontar. The implementation method included five stages: socialization and needs assessment, face-to face training, application implementation, post-training assistance, and evaluation, and program sustainability. The results showed an increase in participants' understanding and skills in using the application. It was evident that participants are able to record savings, loan, and installment transactions digitally, as well as create simple financial reports. The sustainability of this program is expected to help manage the PKK savings and loan unit's finances to be more accountable and efficient.